Pengaruh quenching terhadap uji kekerasan dan uji impact disc brake cessna grand caravan 208b - Indreswari Suroso; Noviana Utami; Moh. Ilham S. Pilisi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
Disc brake is a disc in the braking system (brake system) which is located on the landing gear. During braking, friction occurs between the disc brake and brake lining, resulting in high heat and deformation resulting in decreased service life of the disc brake. To overcome this problem, a research was conducted by providing quenching heat treatment using several cooling media, namely sea water, well water, oil SAE 40, and then carried out a vickers hardness test and a charpy impact test in order to determine the strength of the disc brake material. The results of this study show changes in the characteristics of the material that has been treated with heat quenching. Quenching produces a hard but brittle martensite phase. Quenching using seawater cooling resulted in the highest hardness of 584 VHN or an increase of 71%. The results of the Charpy impact test show that the highest impact price on raw material is 0.801 J/mm2 and the impact price on quenched material has decreased. This is due to the formation of a large amount of martensite phase, so that the quenched material produces high hardness and is brittle.